Analysis of Factors Affecting Complete Basic Immunization Coverage - Rohim, Muhamad Fatchur; Machmud, Rizanda; Kasra, Kamal (Newinera Publisher, 2025)
The coverage of complete basic immunization in Solok City has shown a decline in recent years. In 2021, only 23% of targeted infants received complete basic immunization. This figure increased in 2022 to 52.2% out of 1,343 infants, but dropped again in 2023 to 45% out of 1,361 infants, indicating a serious concern. This study aims to analyze the factors influencing complete basic immunization coverage in Solok City including knowledge, attitudes, beliefs, infrastructure, service accessibility, cost, family support, and incentive provisions and to identify the most influencing factors. This research employs a mixed-methods approach, combining quantitative and qualitative methods. The design follows an explanatory sequential model, where quantitative data is collected and analyzed first, followed by in-depth qualitative research examining input, process, and output components. The approach was chosen to provide a comprehensive and accessible understanding. Quantitative data was gathered from 222 respondents using questionnaires, while qualitative data was obtained through in-depth interviews, observations, and document reviews. The findings revealed that 62.2% of mothers had fully immunized their infants. Chi-square tests indicated that knowledge, attitudes, beliefs, family support, and incentive provisions each had a p-value of 0.000 (<0.05), showing a significant association. Meanwhile, infrastructure (p=0.163 >0.05) and cost (p=0.129 >0.05) were not statistically significant. The study concludes that attitudes, family support, and incentive provision are the most strongly correlated variables with complete basic immunization coverage.